The Role of Trust in Mediating the Effect of Social Media Marketing and Influencer Credibility on the Purchase Intention of Scora Tone Up Products on TikTok - Veronika Marosa Kabut; Rinaldi (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the effect of social media marketing and influencer credibility on purchase intention, with trust as a mediating variable, for Scora Tone Up products on TikTok. A quantitative survey approach was used; data from 206 respondents selected through purposive sampling were analyzed using PLS-SEM with SmartPLS 4. The results show that social media marketing and influencer credibility each have a positive and significant effect on trust and purchase intention, and trust significantly affects purchase intention. Trust partially mediates both relationships, so companies should optimize social-media content, collaborate with credible influencers, and consistently build consumer trust. Keywords: Social Media Marketing, Influencer Credibility, Trust, Purchase Intention, TikTok, Skincare